Newspaper «Zvyazda» as subject of scientific research - Kanyuta, Veronika I. (Journal of the Belarusian State University. Journalism, 2024)
Works of scientific research which subject is newspaper «Zvyazda», a national periodical of Belarus since August 1917, have been analysed. The newspaper history, the features of its operation during various periods of the Belarusian statehood formation, features of examining specific issues in the publications are of interest to both philologists, historians, and hands-on journalists. The newspaper development in the 21st century is part of interest of researchers of the media sphere. The unique history of the publication, the combination of classical traditions of journalism and modern media innovations, the content in the Belarusian language, all this sets newspaper «Zvyazda» apart in the domestic media market, provides the relevant basis for further scholarly elaboration and analysis.
Keywords: journalism; mass media; the newspaper «Zvyazda»; history of domestic journalism; scientific research